Instrumented Assessment of Motor Performance Fatigability During the 6-Min Walk Test in Mildly Affected People With Multiple Sclerosis - Broscheid, Kim-Charline; Behrens, Martin; Bilgin-Egner, Patrizia; Peters, Anita; Dettmers, Christian; Jöbges, Michael; Schega, Lutz (Frontiers in Neurology, 2022)
There are conflicting results regarding the changes in spatio-temporal gait parameters during the 6-min walk test as indicators of gait-related motor performance fatigability in people with Multiple Sclerosis (pwMS). To further analyze if gait-related motor performance fatigability can be quantified using instrumented gait analysis during the 6-min walk test, we investigated: (i) whether gait parameters recorded during the first or second minute were more stable and thus the better baseline to assess motor performance fatigability and (ii) if the minimum toe clearance together with ‘classical’ spatio-temporal gait parameters can be used to quantify motor performance fatigability in people with MS. Nineteen mildly affected people with MS (12 females/7 males; 47.8 ± 9.0 years; EDSS: 2.7 ± 1.0) and 24 healthy controls (15 females/9 males; 48.8 ± 7.6 years) completed the 6-min walk test equipped with inertial measurement units. Data was analyzed using the attractor method to compare stability of gait parameters and, besides ‘classical’ spatio-temporal gait parameters, the minimum toe clearance was calculated as a potential new marker for motor performance fatigability in people with MS as this was shown in healthy older adults. It was found that (i) gait parameters were more stable in the second than in the first minute and (ii) gait-related motor performance fatigability could not be detected based on spatio-temporal gait parameters including the minimum toe clearance. Descriptive analysis indicated a decrease in minimum toe clearance variability, which is assumed to be indicative for motor performance fatigability, towards the end of the 6-min walk test in some pwMS. Future studies should investigate gait parameters for the assessment of motor performance fatigability in pwMS recorded during more intense and/or longer walking protocols taking the level of disability into account. Furthermore, using gait parameters recorded in the first minute of the 6-min walk test as a baseline for the assessment of motor performance fatigability should be avoided.